Cross-cultural adaptation and psychometric evaluation of a German version of the Activity Patterns Scale (APS-GE) in a large sample of patients with chronic musculoskeletal pain - Anne Kästner; Margarete Donhauser; Inga von Freytag-Löringhoff; Frank Petzke (Frontiers in Pain Research)
BackgroundAcknowledging the multidimensionality of pain-related activity patterns led to the development of a new self-report instrument, the Activity Patterns Scale (APS), linking activity pacing to underlying goals. Owing to the scarcity of validated instruments assessing different dimensions of pain-related avoidance, persistence, and pacing behaviors in Germany, our aim was to develop a German version, the APS-GE and to evaluate its psychometric properties in a representative sample of patients with chronic musculoskeletal pain.MethodsThe APS was translated and culturally adapted following the multistep approach recommended by the American Association of Orthopedic Surgeons Outcomes Committee. A comprehensive psychometric evaluation was carried out in 579 patients suffering from chronic musculoskeletal pain. To assess test-retest reliability, the APS-GE was administered twice to a subgroup of patients. Structural validity was tested using covariance and confirmatory factor analysis. To investigate construct and criterion validity, hypotheses were formulated based on the existing literature addressing expected correlations between APS-GE subscales and established questionnaires, and correlations between activity patterns and several functional and psychological outcomes.ResultsActivity patterns varied regarding their test-retest stability. Factor analysis confirmed the multidimensional 8-factor structure proposed previously. For most APS-GE subscales, acceptable construct validity was demonstrated. Interestingly, only 62.5% of hypotheses describing expected associations of activity patterns with functional and psychological outcomes (criterion-related validity) could be confirmed.ConclusionsThe APS-GE appears to be a change-sensitive instrument for the multidimensional assessment of pain-related activity patterns. Remaining conceptual ambiguities should be reevaluated in future studies. Discrepancies to previous investigations regarding the adaptivity of activity patterns could be due to methodological variations across studies. Preliminary implications for putative motivational mechanisms underlying behavioral dimensions are discussed.